Optimalisasi Kesehatan Mental Remaja Melalui Edukasi Aspek Perkembangan Biologis dan Psikoseksual - Jumaini, Jumaini; Wahyuni, Sri; Sari, Niken Yuniar; Huda, Nurul; Rizka, Yulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Adolescence is a transitional age stage from children to adults. In adolescence, a person will experience various changes related to the transition process towards adulthood, such as the biological and psychosexual aspects for a teenager which are very important, because they will determine the quality of teenagers as the next generation of the nation in the future. The aim of this community service activity is to provide knowledge about normal and deviant development in the biological and psychosexual aspects of adolescents. The activity was carried out in Sri Meranti Village with an age range of 12-19 years. There were 30 teenagers involved. The results of the education show that the average score of teenagers' knowledge about biological and psychosexual development of teenagers before education was 7, while the average score after being given education was 8.03, meaning that there was an increase in the knowledge score of 1.03 after teenagers received education about biological and psychosexual development of teenagers. . The impact of this community service is that teenagers are able to understand normal and deviant aspects of biological and psychosexual development so that they can be monitored in order to achieve optimal mental health for teenagers.